PROFITABILITAS BANK DI INDONESIA DENGAN METODE RISK BASED BANK RATING PADA EMITEN PERBANKAN DI BURSA EFEK INDONESIA - Rowland Bismark Fernando Pasaribu; Dionysia Kowanda; Gusti Nyoman Padma Paramitha (Jurnal Riset Akuntansi dan Keuangan, 2017)
This research aims to analze the influence of Risk Based Bank Rating to the Profitability of generalbank go public listed in the Indonesia Stock Exchange.Factor tasted are Non Performing Loan (NPL),Liquidity to Deposit Ratio (LDR), Proportion of the Independent Board of Commisioners, AuditCommittee, Institutional Ownership, Operating Expens and Operating Income (BOPO) and CapitalAdequacy Ratio (CAR) towards Return On Assets (ROA).The sample of this study using purposivesampling method, with the number of sample used were 20 general banks go public listed in theIndonesia Stock Exchange (IDX) in the periode 2008 - 2014. Result of this study indicate that NPL,Audit Committee, and BOPO has significant effect on ROA, while the LDR, proportion of independentboard, institusional ownership, and CAR has no significant effect on ROA. The result of this analysisshowed about 60,3% from the adjusted R2 that ROA can be explained by NPL,LDR,GCG,BOPO, andCAR. The rest 49,7% influenced by other variables outside the model.Keywords: RBBR,ROA,NPL,LDR,GCG,BOPO,CAR